Biotransformation Studies of Agricultural Nitrogen Pollutants in Keduang Watershed - Pujiastuti Peni; Narimo Narimo; Roesleini J Putri (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
The present study seeks to examine nitrogen biotransformation of agricultural wastewater carried out by nitrosomonas and nitrobacter into Ammonia (N-NH3), Nitrite (N-NO2), and Nitrate (N-NO3) in Keduang watershed. Natural capability of the bacteria is necessary to find out to monitor assimilative capacity of the waterbody towards pollutants. Grab sampling technique was applied in agricultural land and Keduang watershed in reference to Indonesian National Standard (SNI) 6989.59:2008. Meanwhile, analysis of N-NO2 was based on Indonesian National Standard (SNI) 06-6989.09-2004, N-NO3 on SNI 6989.79-2011, and N-NH3 on SNI 06-6989.30-2005. The nitrosomonas and nitrobacter were isolated and identified on NA medium considering methods of Capuccino and Sherman (2005). Afterwards, characterization of colony morphology variants was determined, and both gram stain and biochemical test were conducted. A number of 48.8 nitrosomonas colonies/100 mL were identified in samples of agricultural wastewater, which enable to transform Ammonia (N-NH3) of 0.1390 mg/L into Nitrite (N-NO2) of 0.0632 mg/L. Meanwhile, a number of 330 nitrobacter colonies/ 100 mL are capable of transforming Nitrite (N-NO2) into Nitrate (N-NO3) of 0.2168 mg/L. In conclusion, there is a positive relationship between nitrosomonas in transforming Ammonia into Nitrite and nitrobacter in converting Nitrite into Nitrate. Nitrogen pollutants of the agricultural wastewater in Keduang watershed are able to be reduced by both nitrosomonas and nitrobacter.